Analysis of Project-Based Learning in the Fiqih of Worship Course - Abdul Qodir; Hafid Rustiawan; Ahmad Saepudin; Muhammad Ilham; Adib Rubiyad (EDUJAVARE: International Journal of Educational Research, 2025)
A lack of enthusiasm and learning motivation, accompanied by difficulties in understanding course materials, remains a significant challenge in the educational process. This research aims to analyze the implementation, advantages, and disadvantages of project-based learning (PBL) in the Fiqh Ibadah course at the Department of Islamic Education, Faculty of Education and Teaching, Sultan Maulana Hasanudin State Islamic University of Banten. The research method used is qualitative with a case study approach. The research subjects are students and lecturers. Data were collected through observation, interviews, and document analysis. Data analysis methods include data reduction, data presentation, and drawing conclusions. The results of the research show that PBL through Dauroh Janaiz provides comprehensive understanding to Islamic Education students. Students not only acquire theoretical understanding but also can apply it contextually, enhancing motivation to learn, problem-solving skills, collaborative abilities, and source processing skills. However, there are limitations, such as difficulty in selecting the right project, challenges in finding suitable reference sources, and practical constraints in project implementation. Inhibiting factors include lack of attention from lecturers, difficulty in preparing equipment, inappropriate implementation schedules, student delays, and lack of responsibility from some students. Research recommendations include improving guidance and support from lecturers, more intensive involvement from the faculty, increased financial resources, as well as awareness and participation strategies for students to overcome emerging obstacles. This research contributes theoretically and practically to the learning of Fiqh Ibadah in the examined context.